2012
DOI: 10.1088/0963-0252/21/3/034018
|View full text |Cite
|
Sign up to set email alerts
|

A dc non-thermal atmospheric-pressure plasma microjet

Abstract: A direct current (dc), non-thermal, atmospheric-pressure plasma microjet is generated with helium/oxygen gas mixture as working gas. The electrical property is characterized as a function of the oxygen concentration and show distinctive regions of operation. Side-on images of the jet were taken to analyze the mode of operation as well as the jet length. A self-pulsed mode is observed before the transition of the discharge to normal glow mode. Optical emission spectroscopy is employed from both end-on and side-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
1
17
1
2
Order By: Relevance
“…A more effective production of a dc operated plasma jet, with a similar configuration, was recently observed also in the change in the intensity of emission spectra. [50] It has to be noted that the power provided with each pulse is much higher than the average power recorded in our experiments. With the pulsed or self-pulsing operation, fast rising voltage transients might change the electron distribution function toward higher energies.…”
Section: Effect Of Applied Power On No X -Production Ratecontrasting
confidence: 52%
See 1 more Smart Citation
“…A more effective production of a dc operated plasma jet, with a similar configuration, was recently observed also in the change in the intensity of emission spectra. [50] It has to be noted that the power provided with each pulse is much higher than the average power recorded in our experiments. With the pulsed or self-pulsing operation, fast rising voltage transients might change the electron distribution function toward higher energies.…”
Section: Effect Of Applied Power On No X -Production Ratecontrasting
confidence: 52%
“…Previous characterizations of a plasma that is generated from air at atmospheric pressure in a similar microhollow cathode discharge geometry found plasma temperatures of about 2 000 K for discharge currents of 4-13 mA when the gas was not flowing through the discharge channel. [33,50] However, for a flow rate exceeding 100 mL min À1 (at an operating current of 10 mA) does the plasma temperature already drop to values of less than 1 200 K and is decreasing further with increasing flow rate. [33] Overall, previous investigations allow for the reasonable conjecture that for gas flow rates on the order of liters per minute the plasma Figure 6.…”
Section: Mechanisms Of Reactive Species Generationmentioning
confidence: 99%
“…Zhu and Lopez used a mixture of He and O 2 as the working medium gas to conduct plasma microjet spectral characteristics experiments [15], and the results showed that the higher the concentration of the O 2 component in the mixture, the stronger the emission spectrum of OH and O 3 particles in the plasma jet. Wu et al obtained a nonequilibrium plasma via the rotating gliding arc discharge method [16] and studied the effect of the working medium gas on the plasma generated by the sliding arc discharge, in which N 2 and air were used separately as working gases for sliding arc discharge.…”
Section: Introductionmentioning
confidence: 99%
“…14 Extensive experimentation has been performed with plasmas that use room air and noble gases as starting gas materials. 15,16 Additional studies have been performed using cold plasma in order to create plasma-activated water that possesses antimicrobial properties. 10 In this study, the antimicrobial activity of air and mixtures of nonthermal (cold) plasmas using air with vaporized water and ethanol is investigated.…”
Section: Introductionmentioning
confidence: 99%